A potential progenitor for the Type Ic supernova 2017ein. Issue 2 (30th July 2018) - Kilpatrick, Charles D; Takaro, Tyler; Foley, Ryan J; Leibler, Camille N; Pan, Yen-Chen; Campbell, Randall D; Jacobson-Galan, Wynn V; Lewis, Hilton A; Lyke, James E; Max, Claire E; Medallon, Sophia A; Rest, Armin
ABSTRACT: We report the first detection of a credible progenitor system for a Type Ic supernova (SN Ic), SN 2017ein. We present spectra and photometry of the SN, finding it to be similar to carbon-rich, low-luminosity SNe Ic. Using a post-explosion Keck adaptive optics image, we precisely determine the position of SN 2017ein in pre-explosion HST images, finding a single source coincident with the SN position. This source is marginally extended, and is consistent with being a stellar cluster. However, under the assumption that the emission of this source is dominated by a single point source, we perform point-spread function photometry, and correcting for line-of-sight reddening, we find it to have M F555W = −7.5 ± 0.2 mag and m F555W − m F814W =−0.67 ± 0.14 mag. This source is bluer than the main sequence and brighter than almost all Wolf–Rayet stars, however, it is similar to some WC+O− and B-star binary systems. Under the assumption that the source is dominated by a single star, we find that it had an initial mass of 55^+20_-15 M_ . We also examined binary star models to look for systems that match the overall photometry of the pre-explosion source and found that the best-fitting model is an 80+48M⊙ close binary system in which the 80M⊙ star is stripped and explodes as a lower mass star. Late-time photometry after the SN has faded will be necessary to cleanly separate the progenitor star emission from the additional coincident emission.